Erectile dysfunction as a sentinel marker of endothelial dysfunction disease - Bannakij Lojanapiwat (2018)
Introduction: Vascular disease is the major underlying cause of erectile dysfunction (ED). Endothelial dysfunction acts as a marker of "peripheral vascular disease" that occurs prior to clinical vascular disease. ED is the first clinical manifestation of endothelial disease due to the small size of the penile artery. Brachial f low-mediated vasodilation (FMD) is one of the accurate tests for evaluating endothelial function. We compared the endothelial function by FMD between ED patients without clinical signs of vascular disease and non-ED patients. Methods: 41 ED patients and 30 age-matched normal control subjects were assessed for cardiovascular risks and endothelial function. We measured the FMD in order to evaluate the endothelial function, by comparing the percentage change of the brachial arterial diameter after the brachial arterial occlusion. Results: There were no significant differences in baseline characteristics, cardiovascular risks and lipid values between both groups, except that the high-density lipoprotein cholesterol was higher in the control group. The percentage change of the FMD was 8.7 +/- 1.0 percent and 5.1 +/- 0.6 percent in ED patients and control subjects, respectively (p-value is 0.007). Conclusion: ED is the first clinical presentation of sub- cl inical endothel ial dys funct ion disease prior to the appearance of clinical cardiovascular disease or cardiovascular risk factors. ED can be the sentinel marker of early cardiovascular and other systemic vascular diseases and it should thus be employed in preventive strategies.